Distribution and supply logistics - Straka, Martin (Cambridge Scholars Publisher, 2019)
What is logistics? What is distribution and supply? What is supply chain management? Which elements create distribution and supply space? Which aspects affect storage design? Which information technologies are suitable for distribution and supply systems? What costs affect distribution and supply systems? These are just some of the questions explored in this book. In addition to providing theoretical analysis of the problems of distribution and supply, it practically demonstrates the many ways of using of heuristics to solve specific tasks. It brings together eight case studies to investigate.